Phytohemagglutinin and Light-Induced Charge Density Effects on Plasma Membrane of PlectonemaBoryanum - Virjinia, Doltchinkova; Plamena, R Angelova (Journal of New Developments in Chemistry, 2014)
Effects of the plant lectin phytohemagglutinin M (PHA-M) and illumination on the electrophoretic mobility (EPM) and 90°-light scattering of suspension of spheroplasts obtained by lysis of the unicellular diazothrophic cyanobacteriumPlectonemaboryanumwere studied. Cells cultures were grown on media with different iron content: an iron-deficient (denominated as “Fe-starved” culture), an iron-sufficient (“Fe-sufficient”), and a twentyfold iron excess medium (“Fe-excess”). Lectin addition led to a decrease of the membrane charge density and aggregation of the vesicles. Our results indicate significant influence of the Fe2+ and illumination on the lectin-induced decreasing of EPM and light scattering intensity.
Keywords: Surface charge density; Plectonemaboryanum; Electrophoretic mobility; Light scattering; Spheroplasts; Phytohemagglutinin